2011
DOI: 10.2108/zsj.28.550
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lipovitellin 2 as a Tyrosine-Phosphorylated Protein in Oocytes, Eggs and Early Embryos ofXenopus laevis

Abstract: A tyrosine-phosphorylated protein of 33 kDa is shown to be present in the solubilized yolk fraction of Xenopus laevis oocytes, eggs, and early embryos. The phosphoprotein is lipovitellin 2 as demonstrated by immunoprecipitation and mass spectrometry studies, and is termed pp33/LV2. Sub-cellular fractionation and immunoblotting studies demonstrate that pp33/LV2 is stably present in the Triton X-100-resistant and SDS-soluble yolk fractions during oogenesis, oocyte maturation, and early embryogenesis. From after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The mix was magnetically purified and prepared for western blot. Nuclear fraction isolation of X. laevis embryos was performed using differential centrifugation protocols with modifications 64 , 65 . Briefly, stage 18 X. laevis embryo lysates using a 22 G needle and 20 μL homogenization buffer (HB: 250 mM sucrose, 20 mM Hepes, 10 mM KCl, 1 mM EDTA, 1 mM EGTA, 1 mM DTT, phosphatase and protease inhibitors) per embryo.…”
Section: Methodsmentioning
confidence: 99%
“…The mix was magnetically purified and prepared for western blot. Nuclear fraction isolation of X. laevis embryos was performed using differential centrifugation protocols with modifications 64 , 65 . Briefly, stage 18 X. laevis embryo lysates using a 22 G needle and 20 μL homogenization buffer (HB: 250 mM sucrose, 20 mM Hepes, 10 mM KCl, 1 mM EDTA, 1 mM EGTA, 1 mM DTT, phosphatase and protease inhibitors) per embryo.…”
Section: Methodsmentioning
confidence: 99%
“…Other targets of the activated xSrc include Shc (Aoto et al 1999 ), hnRNP K (Iwasaki et al 2008 ), lipovitellin 2 (Kushima et al 2011 ), and pp40, whose identity is not yet demonstrated (manuscript in preparation) (Fig. 14.1 ).…”
Section: Characterization Of Src As a Mediator Of Gamete Interaction mentioning
confidence: 99%
“…It is well known that phosvitin and pp25 are highly serine/threoninephosphorylated proteins that serve as an energy source of oogenesis and early embryogenesis. On the other hand, tyrosine phosphorylation of LV1 (Browaeys-Poly et al 2007) and LV2 (Kushima et al 2011) has recently been demonstrated in Xenopus. In particular, tyrosine phosphorylation of LV2 is unusually stable during oogenesis, oocyte maturation, and early embryogenesis until the removal of yolk-associated materials from swimming tadpole (Kushima et al 2011).…”
Section: Lipovitellin (Lv)mentioning
confidence: 99%
“…On the other hand, tyrosine phosphorylation of LV1 (Browaeys-Poly et al 2007) and LV2 (Kushima et al 2011) has recently been demonstrated in Xenopus. In particular, tyrosine phosphorylation of LV2 is unusually stable during oogenesis, oocyte maturation, and early embryogenesis until the removal of yolk-associated materials from swimming tadpole (Kushima et al 2011). Possible function of tyrosine-phosphorylated form of Xenopus LV1 and LV2 so far suggested is oocyte maturation (Browaeys-Poly et al 2007;Kushima et al 2011), although it's upstream (liver or oocyte) kinase and downstream cellular function is uncertain.…”
Section: Lipovitellin (Lv)mentioning
confidence: 99%